Perancangan Sistem Web Single Level Marketing Toko SR12 dengan Metode Personal XP (PXP) - Sifa Fauziah; Afrizal Zein (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
Skincare Distributor Sr12 is a Distributor that provides herbal beauty products from PT. SR12 Herbal Perkasa. PT. SR12 Herbal Perkasa is a company engaged in the field of herbal & skin care which was established in 2015 by Toni Firmansyah, S. Farm., Apt as the main director, Asrianty Salam, S.Farm as a pharmacist who is responsible for Plant Operational. The Sr12 Distributor Store requires more active and wider marketing to increase sales. To improve marketing, an information system is needed that can make it easier for consumers to find information about product information and marketing of sr12 products. One of the media that is widely used in marketing is a website. A website is a collection of addresses that display interrelated information in the form of text, images, videos, animations, sounds or a combination of all of them that can be accessed using the internet. To build a website, a method is needed. Personal Extreme Programing (PXP) is a software development method that tries to simplify the various stages in the development process so that it becomes more addictive and flexible. Keywords: Information systems, single level, Personal Extreme Programming (PXP)